The Implementation of Basel III and Asset Liability Management on Financial Performance: The Moderating Role of Bank Size - Natashafira Ramadhani; Liana Mangifera (E-Jurnal Akuntansi, 2025)
Facing global economic dynamics and systemic risks, implementing Basel III and Asset Liability Management is crucial for banking resilience. Basel III enhances capital and risk management, while Asset Liability Management sustains asset–liability balance amid market fluctuations. This study analyzes their impact on the financial performance of 20 conventional banks listed on the IDX (2019–2023), with bank size as a moderating variable, using PLS-SEM. Results show both Basel III and Asset Liability Management significantly improve performance, while bank size enhances performance and strengthens the Basel III–performance link. These findings underline the importance of capital, Asset Liability Management, and bank scale for sustainable profitability.